1998
DOI: 10.1161/01.hyp.31.6.1278
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Blood Pressure Sensitivity to Deoxycorticosterone in Mice With Disruption of Bradykinin B 2 Receptor Gene

Abstract: Abstract-The renal kallikrein-kinin system is activated under conditions of mineralocorticoid excess. To evaluate whether endogenous kinins exert a protective role against the development of mineralocorticoid-induced hypertension, we studied the cardiovascular effects induced by long-term administration of deoxycorticosterone (DOC; 0.3 mol/g body wt SC once per week for 6 weeks) or vehicle in transgenic mice (Bk2r Ϫ/Ϫ ) lacking the bradykinin B 2 receptor gene and in wild-type controls (Bk2r ϩ/ϩ ). Under basal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
16
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 30 publications
7
16
0
Order By: Relevance
“…On the basis of these and other results, [2][3][4] we conclude that the kallikrein-kinin system protects both developing and mature animals from salt-sensitive hypertension. The B 2 R-deficient mouse is a monogenetic model that can be used to study the developmental aspects of salt-sensitive hypertension.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…On the basis of these and other results, [2][3][4] we conclude that the kallikrein-kinin system protects both developing and mature animals from salt-sensitive hypertension. The B 2 R-deficient mouse is a monogenetic model that can be used to study the developmental aspects of salt-sensitive hypertension.…”
Section: Discussionsupporting
confidence: 69%
“…3 Additional studies by the same group of investigators found that B 2 R null mice are highly susceptible to mineralocorticoid-induced hypertension. 4 Together, these studies indicate that kinins play an important role in the prevention of salt-sensitive hypertension and that this may be achieved by maintaining renal blood flow under conditions of HS intake.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Either an increased or no change in sensitivity to deoxycorticosterone acetate-salt has been reported for B 2 receptor-deficient mice. 19,20 We found no increases in heart rate or altered baroreceptor control of heart rate in our animals, with or without a high salt diet, as have been described by others. 21,22 We did observe an increase in baroreceptor heart rate reflex activity and sensitivity with the higher salt intake.…”
supporting
confidence: 84%
“…By using 4 mouse strains (129/Sv, C57BL/6, and F1 and F2 intercrosses of 129/Sv × C57BL/6), Hartner and colleagues (2003) showed that 129/Sv mice are more susceptible to the development of DOCA-induced high blood pressure and renal damage than C57BL/6 mice (Hartner et al 2003). In addition, in 129Sv/Ev mice, the renal kallikrein-kinin system, which is activated under conditions of mineralocorticoid excess, exerts a protective role against the development of mineralocorticoid-induced hypertension (Emanueli et al 1998). Whether the protective role of endogenous kinins is greater in C57BL/ 6 mice than in 129Sv/Ev or rats has not been investigated.…”
Section: Discussionmentioning
confidence: 99%